1990
DOI: 10.3164/jcbn.8.75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary intake of gamma-linolenic acid on blood lipids and phospholipid fatty acids in healthy human subjects.

Abstract: SummaryThe effects of a dietary intake of gamma-linolenic acid 18: 3 n-6 (GLA) on blood lipids and phospholipid fatty acids were studied in 25 healthy men. The study was conducted over 4 one-month periods during which the subjects maintained their usual diet of about 2,780 kcal per day consisting of 54.4% carbohydrates, 13.5% proteins, and 32.1% lipids, the last of which included 13% in the form of vegetable oils (40g) and 328 mg of cholesterol. The vegetable oil, the only parameter which was varied during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Furthermore, a linear dose response in the increase of DHLA and GLA was observed in liver and erythrocyte phospholipids with both BO and EPO. This is in good agreement with results obtained in human studies (30,45). Ziboh and Fletcher (45), e.g., showed a dose-related increase of the DHLA content in human neutrophils of volunteers after supplementation with dietary BO.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, a linear dose response in the increase of DHLA and GLA was observed in liver and erythrocyte phospholipids with both BO and EPO. This is in good agreement with results obtained in human studies (30,45). Ziboh and Fletcher (45), e.g., showed a dose-related increase of the DHLA content in human neutrophils of volunteers after supplementation with dietary BO.…”
Section: Resultssupporting
confidence: 93%
“…Seeds of borage, evening primrose and black currant plants contain relatively large amounts of GLA. Several studies have shown that the application of GLA-rich oils results in the accumulation of GLA and its metabolite DHLA in tissue phospholipids (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). In previous studies, GLA-containing oils have been compared by *To whom correspondence should be addressed at F. Hoffmann-La Roche Ltd., VFEH, B.…”
Section: Lipids 27 1018-1023 (1992)mentioning
confidence: 99%
“…On the other hand, GLA feeding as compared with LA feeding increased the levels of n-6 fatty acids, whereas it reduced those of n-3 fatty acids. These findings are consistent with the reports that 20511-3 is more readily converted to longchain n-3 metabolites and incorporated into glycerophospholipids than is 18:3n-3 (2 1-24), whereas 18:3n-6 as compared with 18:2n-6 is more readily converted into long-chain n-6 metabolites (25)(26)(27). Thus, dietary supplementation of post-A6-desaturase n-3 or n-6 fatty acids in place of their parent essential fatty acids significantly enhanced the incorporation of n-3 or n-6 fatty acids into glycerophospholipids in dam tissues.…”
Section: Discussionsupporting
confidence: 94%
“…GLA (18:3 n-6), as compared to 18:2n-6, is even more effective in lowering plasma cholesterol in human and experimental animals (15,16,17). It has been reported that the effect of GLA intake on plasma total cholesterol and LDL-cholesterol is dosedependent in healthy humans (18). Huang et al (16) suggested that the hypocholesterolemic effect of GLA was exerted through enhancing the deposition of plasma cholesterol into liver.…”
Section: Discussionmentioning
confidence: 99%